Evidence - based practice competency among nursing students at the University of Medicine and Pharmacy at Ho Chi Minh City and associated factors - Phuong, Dang Thi Minh; Nguyen, Thi Kim Oanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Evidence - based practice (EBP) in healthcare is an essential trend for improving patient safety and care quality, making it crucial to ensure EBP competency among nursing students. This study aimed to assess EBP competency among nursing students and identify associated factors. Methods: A descriptive cross - sectional study was conducted on 230 nursing students in second, third, and fourth year in the University of Medicine and Pharmacy at Ho Chi Minh City. An online survey questionnaire was emailed to the students during the sampling period from April 24, 2023 to July 3, 2023 Results: The participants had an average age of 21.2 ± 0.97 years. The majority were female (89.1%) and of the Kinh ethnic group (85.7%). The mean score of EBP competency of the students was 3.56 ± 0.39. Specifically, EBP - related competencies of the students were at a moderate level or higher (> 2.61), with the highest mean score observed for attitude at 3.77 ± 0.45. Factors such as research and EBP course grades, confidence levels in information technology skills and English proficiency, frequency of EBP application, completion of the thesis, and participation in research clubs all positively influenced students’ EBP competency (p < 0.05). Knowledge, skills, and attitude regarding EBP are closely related. Students with good knowledge usually have good skills and a positive attitude towards EBP (p < 0.01). Conclusions: Nursing students demonstrated EBP competency at a moderate level or higher. The identified associated factors provide a foundation for enhancing the role of EBP among nursing students.